Global, regional and national burden of asthma from 1990 to 2021: a systematic analysis for the Global Burden of Disease Study 2021 - Liwen Zhang; Jilei Lin; Jing Zhang; ShuHua Yuan; Mingyu Tang; Yong Yin; Hejun Jiang; Guijun Yang; Jiande Chen; Jiajun Yuan (BMJ Open Respiratory Research, 2025)
Background Asthma represents a significant global health challenge, exhibiting considerable variation in prevalence, incidence, mortality and disability-adjusted life years (DALYs) across regions and countries. This study evaluates global, regional and national trends in asthma burden from 1990 to 2021, analysing associations with temporal, geographical and demographical factors.Methods Using open data from the Global Burden of Disease (GBD) database (1990–2021), we analysed changes in asthma prevalence, incidence, mortality and DALYs by gender, age and Socio-Demographic Index (SDI) groups. Joinpoint regression analysis calculated the average annual percentage change (AAPC) and annual percentage change (APC).Results From 1990 to 2021, the age-standardised prevalence and incidence rates of asthma declined by 40.01% and 29.89%, respectively. While asthma deaths increased slightly, the age-standardised mortality rate (ASMR) declined by 46.01%. The highest prevalence was observed in South Asia, East Asia and high-income North America, while low-SDI regions exhibited elevated mortality and DALYs. The age and sex-specific patterns indicated a higher asthma burden among females. The results of the joinpoint analysis indicated a global age-standardised incidence rate increase between 2005 and 2010 for both males and females. The ASMR exhibited a statistically significant decline from 1990 to 2021.Conclusions The global age-standardised rate of asthma burden declined from 1990 to 2021. However, asthma remains a significant public health issue, particularly in regions with lower socioeconomic development. Understanding global and regional trends in asthma can inform future policies and interventions, aiming to promote more equitable prevention, diagnosis and treatment worldwide.